Linear radial structure of reactive energetic geodesic acoustic modes. (4th April 2017) - Qu, Z S; Hole, M J; Fitzgerald, M
Abstract: In this paper we have developed a fluid model to study the radial mode structure of the reactive energetic geodesic acoustic modes (reactive EGAMs), a branch of GAM that becomes unstable in the presence of a cold fast ion beam. We have solved the resulting dispersion relationship, a second order ODE, both analytically in restricted cases and numerically in general. It is found that the reactive EGAM global mode structure is formed with the inclusion of fast ion finite drift orbit effects. In two cases with typical DIII-D parameters but different q profiles, the global EGAM frequency is slightly higher than the local EGAM extremum, located either on axis with a monotonic shear or at mid-radius with a reversed shear. The mode wavelength roughly scales with L orbit 1 / 2 in the core and L orbit at the edge, though the dependency is more complicated for the reversed shear case when L orbit < 0.06 a ( L orbit is the fast ion drift orbit width and a the minor radius). Finally, the growth rate of the global mode is boosted by 50% to 100% when switching from co-beam to counter-beam, depending on the fast ion density, which may help to explain the more frequent occurrence of EGAMs with counter-injection in experiments.